Ответ:
-
Объяснение:
1)
=![\frac{16x+1}{7} \frac{16x+1}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B16x%2B1%7D%7B7%7D)
7(5x-4)=2(16x+1)
35x-28=32x+2
35x-32x=2+28
3x=30
x=10
2) ![\frac{x-4}{5}+ \frac{3x-2}{10} =\frac{2x+1}{3}-7 \frac{x-4}{5}+ \frac{3x-2}{10} =\frac{2x+1}{3}-7](https://tex.z-dn.net/?f=%5Cfrac%7Bx-4%7D%7B5%7D%2B%20%5Cfrac%7B3x-2%7D%7B10%7D%20%3D%5Cfrac%7B2x%2B1%7D%7B3%7D-7)
6(x-4)+3(3x-2)=10(2x+1)-210
6x-24+9x-6=20x+10-210
15x-30=20x-200
15x-20x=-200+30
-5x=170
x=34
3) 4
(1-3a+
)-2a(5-4a+2
)+2a(2a-5)=-8
4a-12
+4
-10a+8
-4
+4
-10a=-8
-16a+0=-8
-16a=-8
a = ![\frac{1}{2} \frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D)